Characterization of Mixed Rice: Nutritional Value, Physicochemical Properties, Organoleptic, and Glycemic Index - Elis Septianingrum; Shinta Dewi Ardhiyanti; Liyanan Liyanan; Bram Kusbiantoro; Dody Dwi Handoko (agriTECH, 2023)
The nutritional and physicochemical value of rice could be enhanced by mixing or combining white and brown rice with various beans. Besides nutritional and functional aspects, it is also crucial to consider organoleptic properties. Therefore, this study aimed to characterize nutritional value (proximate), physicochemical properties, organoleptic and Glycemic Index (GI) of mixed rice. A total of 10 mixed rice formulas, ranging from F1 to F10, and consisting of white rice, brown rice, black rice, aromatic rice, sticky rice, black-eyed peas and mung beans, were determined. These samples were analyzed for proximate, total phenolic compounds, pasting properties, and organoleptic tests (hedonic and ranking tests). Furthermore, 3 selected formulas based on the previous test were then evaluated for GI, and Glycemic Load (GL) was calculated. The results showed that adding black-eyed peas and mung beans (F9 and F10) increased the protein content of mixed rice while higher proportion of black or brown rice (F3 and F4) enhanced the fat content. The amylose content was decreased due to higher proportion of sticky rice (F6 and F8). Based on the hedonic test, the F1-F6 formula had a favorable rating. The ranking results indicated that F9 was better than F10, while F1 and F6 was the best among F1 to F4, as well as F5 to F8. Considering the constituent materials, F1, F6, F9 and commercial low GI rice were selected and tested for GI, and the test results showed 48.2, 54.7, 78.0, and 60.3, respectively. As a result, F1 and F6 have the potential to be developed as mixed rice because they have good nutritional value, physicochemical and organoleptic properties, as well as low GI.